Determinan Penerimaan Aplikasi Atlas (Audit Tools And Linked Archive System) (Studi Pada Kap Bali) - Irawan, Madelaine Kieny Paula (Jurnal Ilmiah Wahana Pendidikan, 2024)
The purpose of this study is to empirically examine the effect of perceived usefulness on the attitude of auditors in using ATLAS, to empirically examine the effect of perceived usefulness on auditors' interest in using ATLAS, to empirically examine the effect of perceived ease of use on the attitude of auditors in using ATLAS, to empirically examine the effect of an auditor's attitude on the auditor's interest in using ATLAS, to empirically examine the effect of subjective norms on the auditor's interest in using ATLAS, to empirically examine the effect of perceived behavioral control on the auditor's interest in using ATLAS. This research is included in associative research with data analysis techniques in this study using Partial Least Square (PLS). The results showed that the perceived usefulness variable had an effect on attitude, the perceived usefulness variable had an effect on interest, the perceived ease variable had an effect on attitude, the attitude variable had an effect on interest, the subjective norm variable had an effect on interest, the perceived behavioral control variable had an effect on interest, the interest variable was influenced by perceived usefulness with attitude as mediation.